Kualitas Laba: Implikasi dari Pengaruh Tenure Terhadap Kualitas Audit - Rini Indriani; Apteerizko Dwi Kusumaputra (Faculty of Economics and Business, Universitas Malikussaleh, 2016)
This study aims to determine whether the effect of tenure on earnings quality with quality audits are used as intervening variables. The existence of inconsistencies in the results of previous studies on the effect of tenure on audit quality such as Myers et al (2003), Manry et al (2008), Carey and Simnett (2006), Wibowo and Rossieta (2009) led to re-examined this issue to see the effect of tenure on audit quality. In addition, this study also looked at the effects of indirect and direct influence of tenure on earnings quality and tenure through a quality audit of the quality of earnings that will be the test whether the simultaneous influence. Tenure in this study are calculated by looking at how many years the KAP to audit a company, while the audit quality measure using current accruals and earnings quality measure using earnings management. Observational data in this study is a manufacturing company of the year 2006-2010 in accordance with predetermined criteria. The results of this study indicate that significant tenure was positively related to audit quality, tenure can be affected indirectly through a quality audit of the quality of earnings, and tenure through the quality audit can simultaneously affect the quality of earnings.Keywords: Tenure, Quality Audit, Quality of Earnings